2013
DOI: 10.1093/scan/nst053
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive competition between threat and reward in the brain

Abstract: In the current functional MRI study, we investigated interactions between reward and threat processing. Visual cues at the start of each trial informed participants about the chance of winning monetary reward and/or receiving a mild aversive shock. We tested two competing hypothesis: according to the 'salience hypothesis', in the condition involving both reward and threat, enhanced activation would be observed because of increased salience; according to the 'competition hypothesis', the processing of reward an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 91 publications
5
53
0
Order By: Relevance
“…It is thus possible that, under threat, maintenance-related processes were unable to capitalize on the beneficial effects of potential reward. This is in line with findings from our recent fMRI study (Choi et al, 2014), where we observed that reward anticipation responses in regions of lateral prefrontal cortex that are believed to be critical for working memory maintenance (Curtis and D’Esposito, 2003) were reduced when participants were simultaneously anticipating the threat of shock.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is thus possible that, under threat, maintenance-related processes were unable to capitalize on the beneficial effects of potential reward. This is in line with findings from our recent fMRI study (Choi et al, 2014), where we observed that reward anticipation responses in regions of lateral prefrontal cortex that are believed to be critical for working memory maintenance (Curtis and D’Esposito, 2003) were reduced when participants were simultaneously anticipating the threat of shock.…”
Section: Discussionsupporting
confidence: 92%
“…1). Based on previous behavioral findings where threat of shock reduced the reward responsiveness in a probabilistic learning task (Bogdan and Pizzagalli, 2006) and our recent fMRI findings (Choi et al, 2014), where we observed that threat of shock reduced reward anticipation related responses in regions that are associated with reward processing (e.g., midbrain and striatum) and working-memory (e.g., lateral prefrontal cortex), we expected that threat would counteract the beneficial effect of reward on task performance.…”
Section: Introductionmentioning
confidence: 94%
“…For example, some human neuroimaging studies have found that nucleus accumbens activation is greater on trials incentivized by contingent gains relative to losses in the monetary incentive delay task (Cooper & Knutson, 2008). In other studies, however, both the accumbens and the VTA respond during anticipation of both monetary losses and gains (Carter, Macinnes, Huettel, & Adcock, 2009; Choi, Padmala, Spechler, & Pessoa, 2013; Cooper & Knutson, 2008), and some studies report even greater responses under aversive than approach motivation (Niznikiewicz & Delgado, 2011). This result is paralleled by animal studies in which nucleus accumbens and ventral tegmental area have been found to reflect both appetitive (desire) and aversive (dread) motivation, although potentially in anatomically segregated subregions (Bromberg-Martin et al, 2010; Lammel et al, 2012; S.…”
Section: Motivational Dimensions and Distinctionsmentioning
confidence: 92%
“…Finally, another study explicitly tested the salience hypothesis by exposing participants to a task in which they were simultaneously told about the chance of winning money (salient) and/or the chance of receiving shock (also salient) (Choi et al 2014). Consistent with the findings from the social support studies above, instead of finding increased activity in salience-related neural regions to the combination of reward and pain together, this study found that the effect of reward was reduced during threat and that the effect of threat was reduced during reward.…”
Section: Making Predictions From the Salience Perspectivementioning
confidence: 99%